Pentingnya Peran Pengelolaan Tenaga Kependidikan dalam Meningkatkan Efektivitas Administrasi Sekolah di SMP Negeri 34 Surabaya - Handayani, Ervina Fitriah; Lutfiya, Khifti; Windasari, Windasari; Cindy, Agustin Hanivia (TSAQOFAH, 2024)
The management of education personnel plays an important role in improving the effectiveness of school administration. This study aims to explore the relationship between the management of education personnel and administrative effectiveness in SMP Negeri 34 Surabaya. Through a qualitative descriptive approach, we use interviews, observations, and documentation studies as data collection techniques. Interviews were conducted with administrative staff, teachers, and principals to gain comprehensive insights. Observations were made in various parts of the school to understand the practice of managing education personnel directly. In addition, documentation studies are used to analyze policies and procedures related to the management of educational personnel. In conclusion, effective management of education personnel is the key to achieving educational goals and improving the quality of administrative services at SMP Negeri 34 Surabaya. In this context, an emphasis on continuous development of management teams and training will be an important step to improve the effectiveness of overall management of education and school administration personnel. The results of the analysis confirm that the management of education personnel has a significant effect on the quality of administrative services and the overall performance of the school. The importance of a well-trained management team and periodic training is highly regarded in improving administrative efficiency. Despite challenges, such as gaps in technology capabilities, strong collaboration and commitment overcame those barriers.